Thermal investigation of vanadium-redox flow battery energy storage system - Lai, Wei (2016)
The present study focuses on the thermal investigation of the all-vanadium redox flow battery (VRB). The basic study is the three parts of heat sources ohmic and overpotential heat, entropic heat, heat from pressure drop under the flow rate and current density different operating conditions. The thermal-hydraulic model has contained the non-uniform of flow rate distribution and reversible entropic heat. Results show that under various ambient temperatures and current densities the model predicts electrolyte temperature accurately. At extremely low flow rates, there are significant temperature gradients in the battery system. However, at relatively high flow rates the electrolyte temperature tends to be the same in different components. Three-stack flow patterns including flow without distribution channels and two cases of flow with distribution channels are compared to investigate their effects on battery performance. By comparing the three flow patterns, it is found that the serpentine-parallel pattern is better and controls the flow rates, pressure drop and electrolyte temperature all at expected levels.